Enrollment of infants born to HIV /aids infected mothers in food supplementation programs - Cunha, Gilmara Holanda da; Galvão, Marli Teresinha Gimeniz (Rev Rene, 2007)
The objective of this study was to review the literature about the enrollment of children born to HIV-infected mothers in governmental programs of food supplementation. The Brazilian literature published from 1995 to 2004 was surveyed, showing that there are no specific milk programs for infants born at risk of HIV infection, with only one type of Union resource being distributed through the Fund to Fund Incentive for States and Municipalities. In the absence of specific programs, alimentary guidelines are very important for mothers who cannot breast-feed, especially when the mothers belong to the less privileged social stratum and face food deficits on a daily basis.